Electroretinography in small animal practice - LIAPIS (Ι. Κ. ΛΙΑΠΗΣ), I. K. (Journal of the Hellenic Veterinary Medical Society, 2017)
During the last years, clinical electrophysiology has considerably improved, allowing the evaluation of the retina and visual pathways. In small animal practice, electroretinography is more useful than other diagnostic techniques for the assessment of retinal function, because of the fact that this method doesn't require patient's cooperation. Electroretinography (ERG) is an electrophysiological technique, which measures the retinal action potentials in response to light stimulation. Flash ERG evaluates the function of outer retina and is performed by the using of flashlight units that uniformly stimulate the retina. The evaluation of ERG requires the well understanding of the morphology as well as the physiologic function of the retina. Furthermore, a number of factors, which can influence the quality of the ERG, are totally controlled during the procedure. Because of the fact that electroretinographic values vary, according to many factors and different diagnostic protocols, comparison of results, obtained from different laboratories, would be difficult. Therefore, each veterinary ERG laboratory obtains its own normal values. ERG is indicated, when retinal disease is suspected. ERG can also help to identify the cause of blindness. In small animal practice, the majority of ERGs are performed on candidates for cataract surgery. Other ERG indications include the early diagnosis of central or generalized progressive retinal atrophy (PRA), the differential diagnosis between the sudden acquired retinal degeneration (SARD) and optic neuritis, the glaucoma and many cases of retinal detachments. Furthermore, ERG is used to evaluate the progression of many retinal disorders.